2018
DOI: 10.1111/jgh.14066
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐proliferation effect of blue light‐emitting diodes against antibiotic‐resistant Helicobacter pylori

Abstract: Background and Aim Infection by Helicobacter pylori is implicated in a wide range of upper gastrointestinal diseases. Owing to the rapid emergence of antibiotic‐resistant strains of H. pylori, the development of novel treatment modalities for antibiotic‐resistant H. pylori infection is a key priority. Blue light‐emitting diodes (LED) may represent a unique option owing to their antimicrobial effect. In this study, we aimed to evaluate the anti‐proliferative effect of blue LED against antibiotic‐resistant H. py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
(74 reference statements)
0
8
0
Order By: Relevance
“…As far as the cellular targets are concerned, our scanning electron images show morphological alterations of the bacterial cell wall after administration of a sub-lethal light dose. This could be the main damage of the photodynamic action, leading to bacterial death through leakage of cellular contents or inactivation of membrane transport systems and enzymes (Caminos et al, 2008;Ma et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as the cellular targets are concerned, our scanning electron images show morphological alterations of the bacterial cell wall after administration of a sub-lethal light dose. This could be the main damage of the photodynamic action, leading to bacterial death through leakage of cellular contents or inactivation of membrane transport systems and enzymes (Caminos et al, 2008;Ma et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial PhotoDynamic Therapy (aPDT) relies on the application of a photosensitizer able to absorb appropriate wavelengths in the visible light range and to react with oxygen molecules inside and around cells, resulting in the production of singlet oxygen or other cytotoxic reactive oxygen species (ROS), which lead to cell death, after inducing photodamage. aPDT can efficiently kill a wide range of bacteria (both antibiotic-susceptible and multi-resistant strains), viruses, fungal, and protozoan parasites (Smijs and Pavel, 2011;Thomas et al, 2015;Wang et al, 2017;Alves et al, 2018;Andrade et al, 2018;Namvar et al, 2019) without causing development of resistance (Al-Mutairi et al, 2018;Ma et al, 2018). This approach is particularly advantageous against bacteria naturally producing and accumulating endogenous photosensitizers such as porphyrins and flavins (Plavskii et al, 2018), physiologically involved in several essential biological functions (e.g., respiration, biological oxidation, photosynthesis, sulfate reduction, metabolism of fats, carbohydrates, and proteins) (Shu et al, 2013;García-Angulo, 2017;Sepúlveda Cisternas et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…H. pylori cells exhibited a short rodshaped morphology after irradiation. [8] The decrease in cell activity and significant increase in ROS indicator fluorescence was observed only in samples exposed to blue LED for up to 2 h.…”
Section: Light Delivery Mode Study Design Outcome Referencementioning
confidence: 92%
“…Im et al (2021) proposed an H. pylori-targeted photodynamic therapy system-p3SLP, which yielded significant antibacterial activity and had no adverse side effects on normal tissues and intestinal flora. Ma et al found that a blue light-emitting diode (LED) could inhibit the proliferation of drug-resistant strains of H. pylori in vitro (Ma et al, 2018). Moreover, LED endoscopic capsules combined with active motion systems have been designed based on the combined action of vision and actuation to move precisely to the target area to kill H. pylori (Luzzi and Tortora, 2022).…”
Section: Antimicrobial Photodynamic Therapymentioning
confidence: 99%